Somatic embryogenesis, organogenesis and assessment of somaclonal variations in mangosteen (Garcinia mangostana L.). - Rineksane, Innaka Ageng (2011)
Mangosteen is one of the most delicious tropical fruits which has an increasing demand due to its wide range of uses. It is used for its medicinal properties such as an antioxidant, antitumoral, anti-inflammatory, antiallergy, antibacterial, antifungal and antiviral. One of the problems related to the establishment of mangosteen plantation is to obtain seedlings throughout the year, which can be solved by micropropagation. In attempts to establish the embryogenic calli of G. mangostana, the potential of uncoated and coated seed explants in forming embryogenic callus was examined in the basal Linsmaier and Skoog (LS) medium supplemented with different auxins at various concentrations. Combinations of cytokinins and 2,4-D in two different media [Murashige and Skoog (MS) and LS] were assessed to improve embryogenicity of calli in mangosteen. Addition of glutamine at various concentrations into MS medium containing 8mg/L 2,4-D and 0.1 mg/L BAP was also carried out to induce embryogenic callus of mangosteen. A study was also carried out to determine the growth and multiplication of cells in suspension cultures and the effect of cytokinins on the advanced formation of embryogenic stages of mangosteen. BAP and NAA were considered for shoot regeneration and the rooting of mangosteen shoots. The most favorable medium for acclimatization of mangosteen plantlets was also produced. The assessment of somaclonal variations among mangosteen plantlets by using RAPD was performed. Uncoated seed explants produced a lower percentage of callus formation (44.23 %), callus score (1.66), fresh weight of callus (59.98 mg) and a lower percentage of contaminated explants (9.7 %) compared to coated seed explants. Among the highest percentage of callus formation (93.3 %) and callus score (3.06) were obtained when uncoated seed explants were cultured on basal LS medium containing 8 mg/L 2,4-D. The calli were yellowish, compact and nodular compared to the spongy loose, whitish and yellowish calli produced on media containing IAA, IBA or NAA. The highest percentage of callus formation (80 %) and the lowest percentage of callus browning (53.53 %) occurred on MS medium supplemented with 8 mg/L 2,4-D and 0.1 mg/L BAP. Although glutamine did not increase the growth of calli, the texture (more friable) and color of callus (more yellowish) were improved. The cells were able to divide and proliferate eventhough cultured in half strength MS liquid medium without 2,4-D. After six months of culture, the heart embryogenic stage was obtained only on medium supplemented with 1 mg/L BAP. The globular and torpedo embryogenic stages were obtained on media supplemented with 1, 3 and 9 mg/L TDZ after five months of culture. Mass production of adventitious shoots was achieved by culturing seed segments of mangosteen on MS solid medium supplemented with 5 mg/L BAP + 0.1 mg/L NAA which produced the highest shoot number (31.7shoots). Forty-one percent of shoots were successfully rooted in MS liquid medium supplemented with 1 mg/L IBA, 60 g/L sucrose and 5 g/L activated charcoal after 4 months. During acclimatization, plantlets grown in medium consisting of organic matter only (A6) showed the highest height difference (7 mm) as compared with other treatments. Stunted shoots with narrow leaves were produced in abundance in MS solid medium supplemented with 5 mg/L BAP + 0.1 mg/L NAA. These shoots were morphologically and genetically different from shoots of other treatments as detected by RAPD marker. RAPD marker effectively recognized the genetic difference among the in vitro shoots and from their mother plant with high level of similarity (80 %). Among the acclimatized plantlets and in vitro shoots, 72 % level of similarity was obtained. The lowest level of similarity (55%) was found between in vivo samples from Serdang and Pahang.